2012
DOI: 10.1016/j.drugalcdep.2011.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the plasma proteome follows chronic opiate administration in simian immunodeficiency virus infected rhesus macaques

Abstract: Background Substantive plasma proteomic changes follow lentiviral infection and disease pathobiology. We posit that such protein alterations are modified during drug abuse, further serving to affect the disease. To this end, we investigated the effect of opiate administration on the plasma proteome of Indian-strain rhesus monkeys infected with simian immunodeficiency virus (SIV) strain smm9. Methods Whole blood was collected at 7 weeks prior to and 1.4 and 49 weeks after viral infection. Viral load, CD4+ T c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Although it does not remove all variabilities, this model provides more consistent results. Non-human primates as an animal model have been used mostly in the context of simian immunodeficiency virus (SIV) infection, mimicking HIV-1 infection in humans [ 39 - 42 ]. A recent study by Niu et al .…”
Section: Experimental Modelsmentioning
confidence: 99%
“…Although it does not remove all variabilities, this model provides more consistent results. Non-human primates as an animal model have been used mostly in the context of simian immunodeficiency virus (SIV) infection, mimicking HIV-1 infection in humans [ 39 - 42 ]. A recent study by Niu et al .…”
Section: Experimental Modelsmentioning
confidence: 99%
“…In terms of viral infections, Dengue fever, Hepatitis B and C, HIV and Simian immunodeficiency virus (SIV) have been studied using iTRAQ of plasma and serum samples. Liu et al compared plasma from individuals with chronic hepatitis B virus‐associated hepatocellular carcinoma (HCC), non‐malignant cirrhosis, chronic hepatitis B, and healthy individuals.…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…Collectively the applications of isobaric labeling of the plasma proteome have ranged from cancer to autoimmune diseases, as well as the influence of life style (smoking and nutrition) and environmentally influenced afflictions (occupational exposure). The references included in this review have not been restricted to human plasma, as for example ape models have been used to study the effect of viral infections, xenographs have been made for tumor models, and other animal‐based disease models (rat or mouse). In addition to regular profiling of the plasma proteome, some studies have targeted glycosylation and carbonylation .…”
Section: Applications Of Isobaric Labeling For Serum and Plasma Protementioning
confidence: 99%
“…Various methods involving depletion of the most abundant proteins have been proposed. Among the immunedepletion methods, use of IgY columns seems to be the most efficient [27,94,95] as well as the ProteoMiner kit from BioRad (Hercules, CA), which depletes serum albumin in a cleaned-up sample [47]. Other methods of plasma sample enrichment were also used.…”
Section: Proteomics Of Body Fluids From Hiv-1 Infected Individualsmentioning
confidence: 99%
“…Out of them, 64 proteins showed statistically significant differences in expression and represented inflammatory responses to microbial infections. In the subsequent study [95] in which the effect of opiate administration on the course of acute and chronic SIV infection of monkeys was investigated, a relatively small subset of proteins were identified and quantified and the majority of proteins also represented inflammatory responses to microbial infections. Despite using a well-controlled animal model and reduced technical variability as much as possible, the authors still observed highly variable changes in the plasma proteome, which they linked to differences in genetic background and individual responses to exogenous conditions-an opiate administration.…”
Section: Proteomics Of Body Fluids From Hiv-1 Infected Individualsmentioning
confidence: 99%